Animal Scavenging as Social Metaphor: A Carved Chlorite Vessel of the Halil Rud Civilization, Kerman, Iran, Mid Third Millennium bc. Issue 4 (November 2021) - Vidale, Massimo; Eskandari, Nasir; Shafiee, Mojgan; Caldana, Irene; Desset, Francois
Abstract : A fragmentary large chlorite vessel of the Halil Rud valley civilization (Kerman, Iran, mid third millennium bc ), found in unknown circumstances and recently recovered by the police forces of Iran, is discussed in the wider scenario of coeval animal iconographies of middle and southwest Asia. Beginning from the imagery carved in the two superimposed friezes of the reassembled fragments, we review the different theoretical approaches in interpretation of similar animal iconography. The figuration of the vessel is interpreted as a scene of the scavenging of bovine carcasses by three different animal actors: lions and birds of prey/vultures, but also hyenas—a subject previously unknown in the art of the reference regions. Following a review of the interrelations of these species in scavenging and with humans, particularly in the coeval context of domestic animal exploitation and developing urban settlement, we investigate the potential semantic implications of the iconography in terms of the symbolism and ideology in the social context.